2023
DOI: 10.1002/aenm.202300837
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐Entropy Metal Selenides Nanoparticles with Optimized Electronic Structure as High‐Performance Bifunctional Electrocatalysts for Overall Water Splitting

Abstract: Development of low-cost and high-efficiency electrocatalysts for overall water splitting is of great significance in the sustainable hydrogen economy. Herein, Fe 1.2 (CoNi) 1.8 Se x medium-entropy metal selenides (MESes) nanoparticles are prepared via the selenylation of metal-organic frameworks (MOFs) precursors. The optimal Fe 1.2 (CoNi) 1.8 Se 6 MESe exhibits an outstanding electrocatalytic performance in alkaline media, offering low overpotentials of 66 and 216 mV at 10 mA cm −2 for the hydrogen evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…It has been observed that the transfer of electrons on the surface of the FeNiMnO 4 /CeO 2 heterojunction is more pronounced than that on FeNiMnO 4 , which facilitates bond activation. 67,68 Fig. 5c illustrates the two-dimensional plane charge density difference (Δ ρ ) that was obtained to provide a more intuitive understanding of the charge transfer process.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that the transfer of electrons on the surface of the FeNiMnO 4 /CeO 2 heterojunction is more pronounced than that on FeNiMnO 4 , which facilitates bond activation. 67,68 Fig. 5c illustrates the two-dimensional plane charge density difference (Δ ρ ) that was obtained to provide a more intuitive understanding of the charge transfer process.…”
Section: Resultsmentioning
confidence: 99%
“…4d). 100 The best Fe 1.2 (CoNi) 1.8 Se 6 showed excellent electrocatalytic properties in alkaline media. Compared with MOF precursors, the formation of medium-entropy nanoparticles increased the surface charge density and brought the D-band center closer to the Fermi level.…”
Section: Mof-based Materials For Electrocatalytic Water Splittingmentioning
confidence: 94%
“…Wu et al prepared Fe 1.2 (CoNi) 1.8 Se x MEM using the solvothermal method. 28 29 Therefore, medium-entropy catalysts can combine the benefits of each element and demonstrate remarkable catalytic performance. Unlike powder catalysts that need to be fixed on electrodes using binders, self-supporting electrocatalytic materials are directly grown on conductive substrates without the need for binders, thus avoiding the problems of the blockage of catalytically active sites aroused by the binders and the exfoliation from the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The electrons tend to be enriched in Fe-dominated metal sites after the introduction of C/N, leading to excellent OER activity due to the weakened adsorption of the electron-rich metal sites. Wu et al prepared Fe 1.2 (CoNi) 1.8 Se x MEM using the solvothermal method . DFT calculations indicated that the center of the d-band of the metal was approaching the Fermi level, which effectively enhanced the adsorption and desorption of *H on the catalyst surface, thus reducing the Gibbs free energy.…”
Section: Introductionmentioning
confidence: 99%